Examining the streams of a retention policy to understand the politics of high-stakes reform. - Brown, Christopher P. (Education Policy Analysis Archives, 2007)
Using John Kingdon's (2003) multiple streams approach to agenda setting, I analyze how key actors within the state of Wisconsin understood the need to construct and implement the state's No Social Promotion statutes to improve students' academic performance. Policymakers within the state focused their standards-based reforms on the issue of improving students' academic performance through increasing accountability. In doing so, they did not see these high-stakes policies as a form of punishment for those who fail, but rather, as a tool to focus the education establishment on improving the academic skills and knowledge of all their students. Thus, the retained student is not the primary concern of the policymaker, but rather, the retained student demonstrates the state's system of accountability works. Raising the question as to whether those who support or oppose high-stakes policies such as these should focus their efforts on the agenda setting process rather than analyzing effects of such policies. I contend that while evaluating a policy's effects is important, education stakeholders must pay attention to all three streams of the agenda setting process as they promote particular reforms to improve students' academic performance.